Strategi Komunikasi Pemasaran Asuransi Syariah - Aida Malan Sari; Nuri Aslami (Transformasi Manageria: Journal of Islamic Education Management, 2022)
This article contains a Sharia Insurance Marketing Communication Strategy which focuses on the stages of developing effective marketing communications, namely determining the target audience, setting communication goals, designing messages, selecting media, selecting message sources, determining the promotional mix. and determine the marketing mix strategy. The research method used is a qualitative descriptive method with data analysis techniques using the Interactive model of Matthew B. Miles and A. Michael Huberman. The results showed that a marketing communication strategy that prioritizes two-way communication with customers to sell their products in order to gain influence, trust, and actions such as direct feedback can have a positive impact. development of effective marketing communications. to achieve the goals that have been set and can be implemented properly. Keywords: marketing strategy, marketing communication, sharia insurance